ON THE HISTORY OF ESTABLISHMENT OF THE FIRST PEDIATRIC FACULTY IN RUSSIA AND PEDIATRICIAN PREPARATION - N.V. Polunina ("Paediatrician" Publishers LLC, 2006)
The article highlights the stages of pediatric educational system formation in Russia from the 19th century till now. The author stresses the importance of pediatrician preparation at the prediploma level.Key words: education, pediatry.